Mild and Efficient One-Pot Synthesis of 2‑(Perfluoroalkyl)indoles by Means of Sequential Michael-Type Addition and Pd(II)-Catalyzed Cross-Dehydrogenative Coupling (CDC) Reaction - Shen, Dandan; Han, Jing; Chen, Jie; Deng, Hongmei; Shao, Min; Zhang, Hui; Cao, Weiguo (Organic letters, 2015)
2-Perfluoroalkylated indoles were efficiently synthesized via a one-pot cascade Michael-type addition/palladium-catalyzed intramolecular cross-dehydrogenative coupling (CDC) process, using molecular oxygen as the sole oxidant at 100 °C in DMSO. This process allows atom economical assembly of indole rings from inexpensive and readily available anilines and methyl perfluoroalk-2-ynoates and tolerates a broad range of functional groups.